Insurance Brokers’ behaviour: the effect of policy collection on management decisions - Latorre Guillem, Miguel Ángel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Spanish legislation on insurance and reinsurance mediation stipulates that intermediary can only receive commissions and fees for the management of their policies and prohibits any other form of remuneration. However, it is possible that financial intermediaries who manage larger risks wait until the end of the legal deadline to settle with insurance companies. This common practice in the insurance market hides additional remuneration in defiance of the law. It also means that the risk is not covered within the prescribed period and would, involve a commercial payment to the client, and, on the other hand, affect sustainable claims management.